Epigenetic Contributions to the Relationship between Cancer and Dietary Intake of Nutrients, Bioactive Food Components, and Environmental Toxicants - Su, L. Joseph; Mahabir, Somdat; Ellison, Gary L.; McGuinn, Laura A.; Reid, Britt C. (Frontiers in Genetics, 2012)
Epigenetics is the study of heritable changes in gene expression that occur without a change in DNA sequence. Cancer is a multistep process derived from combinational crosstalk between genetic alterations and epigenetic influences through various environmental factors. The observation that epigenetic changes are reversible makes them an attractive target for cancer prevention. Until recently, there have been difficulties studying epigenetic mechanisms in interactions between dietary factors and environmental toxicants. The development of the field of cancer epigenetics during the past decade has been advanced rapidly by genome-wide technologies – which initially employed microarrays but increasingly are using high-throughput sequencing – which helped to improve the quality of the analysis, increase the capacity of sample throughput, and reduce the cost of assays. It is particularly true for applications of cancer epigenetics in epidemiologic studies that examine the relationship among diet, epigenetics, and cancer because of the issues of tissue heterogeneity, the often limiting amount of DNA samples, and the significant cost of the analyses. This review offers an overview of the state of the science in nutrition, environmental toxicants, epigenetics, and cancer to stimulate further exploration of this important and developing area of science. Additional epidemiologic research is needed to clarify the relationship between these complex epigenetic mechanisms and cancer.